2020
DOI: 10.1016/j.ijporl.2020.110463
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent tonsillitis and parental perceptions of tonsillectomy during the COVID-19 pandemic

Abstract: Objectives The coronavirus outbreak has triggered the implementation of nationwide social distancing measures. We aimed to investigate the impact on patients with recurrent tonsillitis and parental perceptions towards tonsillectomy during the COVID-19 pandemic. Methods A telephone questionnaire was conducted for all children awaiting tonsillectomy for recurrent tonsillitis after social distancing for 2 months at our centre. The COVID-19 lockdown period was compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 6 publications
3
13
1
Order By: Relevance
“…However, we did not observe the same trend in the number of patient encounters related to acute tonsillitis. This is in contrast to another study, which found a reduction in tonsillitis episodes during a 2-month period of social distancing in a pediatric population [ 29 ].…”
Section: Discussioncontrasting
confidence: 99%
“…However, we did not observe the same trend in the number of patient encounters related to acute tonsillitis. This is in contrast to another study, which found a reduction in tonsillitis episodes during a 2-month period of social distancing in a pediatric population [ 29 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Recurrent throat infections and obstructive disorders are indications for tonsillar surgery, while indications for tympanostomy are recurrent middle ear infections and persistent effusion 9,10 . In a survey of the tonsillectomy waiting list in the pediatric population, tonsillitis episodes diminished during the 2 months of social distancing in the UK 11 . Nevertheless, all patients from the waiting list were operated on electively either during or after the lockdown.…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 10 In a survey of the tonsillectomy waiting list in the pediatric population, tonsillitis episodes diminished during the 2 months of social distancing in the UK. 11 Nevertheless, all patients from the waiting list were operated on electively either during or after the lockdown. Several studies have demonstrated a decrease in the number of acute otitis media in children during the lockdown, 3 , 4 , 12 , 13 also in recurrent cases.…”
Section: Introductionmentioning
confidence: 99%
“…Adenotonsillar surgery is the second most common surgery in children, after MTT [ 32 , 37 ]. Similar to otitis media, data has shown that masking and social distancing may have decreased episodes of tonsillitis in children with recurrent tonsillitis [ 38 ]. Initially, all tonsillectomy procedures save those for severe OSA or concern for malignancy, were recommended to be postponed [ 16 ].…”
Section: Discussionmentioning
confidence: 99%